Goethe e la Bildung, tra arte, natura, educazione - Marco Giosi (Firenze University Press, 2022)
The article reflects on the concept of Bildung during the 19th century and how it is central to Goethe's works, representing the fundamental pivot of human evolution. In particular, it investigates the poetics of the sublime and the forms of Art and Nature as mirrors of the self and the significance of the novel of formation, beginning with the Wilheilm Meister. Goethe, in fact, can be regarded as one of the "fathers" of the coming-of-age novel.These themes are then intertwined with the role of theater, which, together with poetry and drama, represent a means of freely and fully developing the human personality.